Cooperative competition? The ambivalence of coopetition in territorial authorities. (September 2019) - Assens, Christophe; Bartoli, Annie; Hermel, Philippe
Cooperative competition – coopetition – is a phenomenon whose influence extends to the sphere of territorial public management. Based on an initial questionnaire conducted among 252 territorial authority managers, an exploratory case study on inter-municipal cooperation in France's Rhône-Alpes region, and an in-depth follow-up survey among 10 leaders, we analyse why and how cooperation between territorial authorities is advisable, despite the potential political rivalry between local elected representatives and the specific challenges of each territory, provided that they respect the principles of equity in governance and avoid conflicts of interest when managing their teams. Points for practitioners: Our research shows the benefits of cooperation between competing territorial authorities, provided that they respect the principles of equitable management. This implies the need to distribute power equally among partners of all sizes, to take decisions collectively by a majority, or even unanimously when it comes to a change of governance, and not to infringe on the prerogatives of each partner, unless added value can be gained from pooling the efforts of territorial authorities.